Study of the genus Opius Wesmael (Hymenoptera: Braconidae: Opiinae) in Southern Iran, with eleven new records - Ameri, Ali; Talebi, Ali Asghar; Rakhshani, Ehsan; Beyarslan, Ahmet; Kamali, Karim (Zootaxa, 2014)
This study was carried out to determine the species of the genus Opius Wesmael, 1835 in Hormozgan province (Southern Iran). Malaise traps and sweep nets were used to obtain adult specimens from various habitats in Hormozgan province during 2011–2013. Fifteen species from the genus Opius belonging to ten subgenera were collected. The subgenera Merotrachys Fischer, 1972 and Opiostomus Fischer, 1972 and eleven species are recorded for the first time from Iran: Opius (Agnopius) nowakowskii Fischer, 1959; Opius (Agnopius) novosimilis Fischer, 1989, Opius (Allophlebus) staryi Fischer, 1958; Opius (Allotypus) damnosus Papp, 1980; Opius (Opiostomus) riphaeus Tobias, 1986; Opius (Opiothorax) minusculae Fischer, 1967; Opius (Pendopius) bajariae Fischer, 1989; Opius (Merotrachys) penetrator Fischer 1966; Opius (Hypocynodus) flavipes Szepligeti, 1898; Opius (Hypocynodus) latidens Fischer, 1990 and Opius (Hypocynodus) latipediformis Fischer 2004. A key for identification of Opius species from southern Iran is provided.